2015
DOI: 10.1021/acsmedchemlett.5b00462
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Medicinal Chemistry

Abstract: ABSTRACT:The past decade has seen tremendous growth in our understanding of epigenetics and chromatin remodeling. Small, organic molecule modulators of a number of chromatin modifying proteins (CMPs) have been reported over this time frame and several of these have advanced to human clinical trials. In this Viewpoint, I summarize the current state of medicinal chemistry efforts focused on epigenetic targets and attempt to provide some insight into future directions on which the community may wish to focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…SAM itself is a very polar molecule, and developing inhibitors that are sufficiently polar to exploit the SAM-binding site but sufficiently hydrophobic to cross cell membranes has proven difficult. It may therefore seem surprising that PMT inhibitors in clinical trials to date are cofactor competitors of the H3K79 PMT DOT1L, a methyltransferase that is aberrantly recruited to leukemogenic loci in MLL-translocated leukemia, and of the H3K27 PMT EZH2, which carries a gain of function mutation in some lymphomas (Copeland, 2016). Recent structural studies have revealed how these compounds overcome the hydrophilicity challenge of the cofactor-binding pocket.…”
Section: Substrate and Cofactor Site Inhibitorsmentioning
confidence: 99%
“…SAM itself is a very polar molecule, and developing inhibitors that are sufficiently polar to exploit the SAM-binding site but sufficiently hydrophobic to cross cell membranes has proven difficult. It may therefore seem surprising that PMT inhibitors in clinical trials to date are cofactor competitors of the H3K79 PMT DOT1L, a methyltransferase that is aberrantly recruited to leukemogenic loci in MLL-translocated leukemia, and of the H3K27 PMT EZH2, which carries a gain of function mutation in some lymphomas (Copeland, 2016). Recent structural studies have revealed how these compounds overcome the hydrophilicity challenge of the cofactor-binding pocket.…”
Section: Substrate and Cofactor Site Inhibitorsmentioning
confidence: 99%
“…Many studies have confirmed the implication of epigenetics in the development, persistence and progression of many diseases such as neurodegenerative disorders, autoimmune diseases and inflammation, cancers and viral infections [2][3][4][5]. This great implication of epigenetic factors in various disease states has rendered them an interesting target for the development of novel therapeutics [6,7]. An important player in the modelling of the cellular epigenetic map are the class of histone modifiers.…”
Section: Introductionmentioning
confidence: 98%
“…The American Chemical Society is to be congratulated for this ambitious endeavor, yet the articles represented in this and the other journal’s special issues represent merely a starting point for the detailed, quantitative understanding of chromatin biochemistry and its application to the development of new medicines. This is a fertile ground for new research, as there remain many unanswered questions about the biochemical processes of chromatin remodeling, the biochemical and biological interdependence of these various reactions in the precise control of gene transcription, and the biochemical basis for diseases that result from alterations of these control mechanisms . In the area of biochemical processes for chromatin remodeling, a large number of enzymes that catalyze mechanisms of remodeling and proteins that respond to such remodeling remain to be investigated in biochemical detail.…”
mentioning
confidence: 99%
“…Yet, the role of conformational dynamicsvia inter- and intra-assembly protein–protein interactionsin translating binding into transcriptional modulation by these complexes remains to be described fully. It is increasingly clear that the transcriptional impact of a specific chromatin mark cannot be understood in isolation but rather depends on the background of other chromatin marks that may be occurring simultaneously within the cell nucleus. ,,, The nature of these chromatin mark interdependencies and their further dependence on non-chromatin-based signaling pathways in cells need to be investigated further if we are to understand these myriad processes and their roles in normal physiology and pathobiology. Many of these questions may best be answered by chemical biology approaches, utilizing potent and highly selective modulators of specific chromatin-modifying proteins (CMPs).…”
mentioning
confidence: 99%
See 1 more Smart Citation